Superconducting motors for aircraft propulsion: the Advanced Superconducting Motor Experimental Demonstrator project. (July 2020) - Grilli, Francesco; Benkel, Tara; Hänisch, Jens; Lao, Mayraluna; Reis, Thomas; Berberich, Eva; Wolfstädter, Simon; Schneider, Christian; Miller, Paul; Palmer, Chloe; Glowacki, Bartek; Climente-Alarcon, Vicente; et al.
Abstract: The European Union-funded Advanced Superconducting Motor Experimental Demonstrator (ASuMED) project started in May 2017 with the purpose of demonstrating the benefits of a new, fully superconducting motor for reaching the targets established by the Flightpath 2050 plan. The project aims at a motor power density of 20kW kg −1 using a high-temperature superconducting (HTS) stator. The rotor will use HTS stacks operating like permanent magnets. A highly efficient cryostat for the motor combined with an integrated cryogenic cooling system and associated power converter will be used. This article provides a general overview of the prototype that is currently being assembled and that will be tested soon.